PENGARUH PERMAINAN LABIRIN NUMBER TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA PANGEAN KABUPATEN KUANTAN SINGINGI - Desi Wahyuni; Devi Risma; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the observations in the field against the ability to know the concept of number of protégés have not evolved with the optimal. To do so use the game maze number. The purpose of the study is to investigate the influence of labyrinth number against the ability to know the concept of number of children ages 4-5 years. This research was conducted at TK Negeri Pembina Pangean Regency Kuantan Singingi from January until April 2019 2019 for observation and research. This research is experimental research design using one group pretest and posttest design with a total sample of 15 children. . Data collection techniques used in this research is the use of observation sheet the ability to know the concept of number. Data analysis techniques using a t-test test by using SPSS program ver 20. From the results of the analysis of the data obtained thitung of larger 12.895 dati ttabel = 2.145 with sig 0000 < 0.05. It can be concluded that there is a difference in the ability to know the concept of significant numbers before and after using a maze game number. Based on the hypothesis test is obtained there is influence of labyrinth number against the ability to know the concept of numbers in children ages 4-5 years at TK Negeri Pembina Pangean Regency Kuantan Singingi.Key Words: Maze Number, The Ability To Know The Concept Of Numbers